Implementasi Digital Marketing dalam Model Pembelajaran Santripreneur untuk Meningkatkan Kemandirian Ekonomi Santriwati Pasca-Pesantren - Mohammad Najib Roodhi; Gilang Primajati; Zamroni Alpian Muhtarom; Kurnia, Juan; Ghina Aurelia Rachman (Pendidikan Matematika, FKIP Universitas Mataram, 2025)
This community service activity focuses on the implementation of the digital marketing aspect of the Santripreneur learning model based on digital technology and financial literacy for female students at Madrasah Aliyah Putri Hikmatusysyarief NWDI Salut, West Lombok. The training is designed to improve the skills of female students in product promotion, branding, and online marketing through the use of digital platforms such as Instagram, WhatsApp Business, and the live practice site https://hiksypreneur.site/. Activities include socialization, technical training, marketing content practice, and evaluation of success through a pre-post test survey. The results show an increase in the ability of female students in creating digital content (+78%), managing business accounts (+72%), and understanding online marketing strategies (+81%). The application of digital marketing has proven to be an effective means of fostering economic independence after Islamic boarding school through strengthening business identity and technology-based market access.